Parâmetros para a identificação e controle dos documentos digitais: aportes da diplomática contemporânea - CASSIANO, Nélderson (2017)
Analysis of the types of formats of digital documents and your relation with the Archival Diplomatic, with the purpose of establishing subsidies for the organization of documents produced in a digital environment. The kind of research shall be made in the form of literature review, through articles and books written by Brazilian authors and international. The concept of the inseparability of support is presented. It is possible to differentiate digital objects from digital documents and archival documents. Reaffirms the interdisciplinary ties between Archival, Diplomatic and Computing through the document concept. Adds and demonstrates the Diplomatic Analysis of conventional archival documents for digital.